Distribution of water-stable aggregates and aggregating agents in oxisols of the Brazilian cerrados - Neufeldt, Henry; Ayarza, Miguel Angel; Resck, DVS; Zech, W. (International Center for Tropical Agriculture, 1999)
The effects of land-use change on the structure of Oxisols in the Brazilian savannas (also known as the Cerrados) are still insufficiently understood. We therefore studied loamy and clayey Oxisols under natural savanna, crop, pasture, and reforestation to (1) quantify management-induced changes in the quantity of water-stable aggregates, (2) identify the main aggregating agents, and (3) correlate aggregation with changes in pore-size distribution. Clayey soils showed a significantly higher macroaggregation than did loamy soils. Compared with natural savanna, macroaggregation was clearly reduced under crops, whereas aggregation of soils under pasture and tree plantations was only slightly affected. In both clayey and loamy soils, polysaccharides formed the main aggregating agent. In the clayey soils, lime very effectively disaggregated the soils by weakening the electrostatic forces between positively and negatively charged soil compounds. In the loamy soils, the role of roots in binding macroaggregates was significant. Because pastures provide strong rooting and high polysaccharide production, we recommend introducing crop/pasture rotations. Management-induced disaggregation strongly affected the pore-size distribution by compacting the soils, and thus reducing macroporosity and increasing mesoporosity. Microporosity, however, was unaffected by management and differed only between the two substrates. Considering the Oxisols` typically low pore space at plant-available matrix potentials, the increase in mesoporosity may be important for annual crops during the frequent dry spells in the rainy season.